PENGARUH USIA, JENIS KELAMIN, TEMAN, DAN ORANG TUA TERHADAP KESEPIAN PADA REMAJA DAN DI INDONESIA (ANALISIS DATA GSHS TAHUN 2015): PENGARUH USIA, JENIS KELAMIN, TEMAN, DAN ORANG TUA TERHADAP KESEPIAN PADA REMAJA DAN DI INDONESIA (ANALISIS DATA GSHS TAHUN 2015) - Feniati Rahayu Aisyah (Jurnal Medika Hutama, 2022)
Adolescence undergoes many changes that can lead to loneliness in its development. Loneliness can occur due to the influence of age, gender, friends and parents. The purpose of this study was to determine loneliness and its relationship with age, gender, peer influence, and parental influence. This study uses secondary data from the 2015 GSHS which is the result of collaboration between WHO and the Indonesian Ministry of Health with 9,604 respondents. This study shows that loneliness is related to older age, women, victims of bullying, not having close friends, getting support from friends, parents understand the problem and parents know free time. Logistic regression analysis showed that the variable being bullied had the strongest relationship with loneliness in adolescents. There is a need for intervention by targeting increasing parental support skills, helping adolescents develop friendship skills, providing counseling, and preventing victims of bullying on ​​adolescents in Indonesia.